2000
DOI: 10.1038/sj.bjp.0703728
|View full text |Cite
|
Sign up to set email alerts
|

Human renal mesangial cells are a target for the anti‐inflammatory action of 9‐cis retinoic acid

Abstract: 1 Mesangial cells play an active role in the in¯ammatory response to glomerular injury. We have studied in cultured human mesangial cells (CHMC) several eects of 9-cis retinoic acid (9-cRA), an activator of both retinoic acid receptors (RARs) and retinoid X receptors (RXRs). 2 9-cRA inhibited foetal calf serum-induced CHMC proliferation. It also prevented CHMC death induced by the in¯ammatory mediator H 2 O 2 . This preventive eect was not due to any increase in H 2 O 2 catabolism and it persisted even when bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 56 publications
(66 reference statements)
0
25
0
Order By: Relevance
“…For example, RXR agonists inhibited apoptosis in human mesangial cells exposed to H 2 O 2 and naive tlymphocytes. [14,15] However, they facilitated apoptosis in tumor cells, such as lung and breast carcinomas, lymphomas, and leukemias. [16][17][18] Thus, there is controversy over pro-or anti-apoptotic effect, which may depend on the type of cells and the nature of the apoptotic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RXR agonists inhibited apoptosis in human mesangial cells exposed to H 2 O 2 and naive tlymphocytes. [14,15] However, they facilitated apoptosis in tumor cells, such as lung and breast carcinomas, lymphomas, and leukemias. [16][17][18] Thus, there is controversy over pro-or anti-apoptotic effect, which may depend on the type of cells and the nature of the apoptotic stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Human mesangial cells (HMCs) were obtained from adult kidney tissue, as we have previously described, and were used between passages 8 and 12 (28). An immortalized human mesangial cell line (HMCL) was developed by Professor J. D. Sraer (Hôpital Tenon, Paris, France) (41) and is a kind gift from Dr. Xiongzhong Ruan (Royal Free and University College Medical School, London, UK) (35).…”
Section: Methodsmentioning
confidence: 99%
“…Antihypertrophic effect of retinoic acid-mediated signaling has been demonstrated in myocardial cells in response to angiotensin II, endothelin-1, and phenylephrine (28,29). Retinoic acid functions by binding to nuclear receptor proteins, the retinoic acid receptor (RAR), and the retinoid X receptor (RXR) family, which are expressed in a variety of cell types and act as transcription factors upon ligand binding (30,31). Previous studies have shown that retinoic acid receptors also interact with other transcription factors to mediate gene expression (32,33).…”
Section: Atrial Natriuretic Peptide (Anp)mentioning
confidence: 99%